ROLE, COMPETENCE, AND RESPONSIBILITY OF THE PROFESSORS IN THE CONTEMPORARY ACADEMIC ECOSYSTEM - Moneva, Iva (E-Journal VFU, 2025)
This article explores the transformation of the university professor’s role within the context of a changing academic ecosystem and the cognitive characteristics of Generation Z. Based on empirical data, it argues for a shift from the traditional lecture-based model toward the facilitation of active, visual, and practice-oriented learning. A comparative framework between lecturer and facilitator is presented, emphasizing the importance of interactive methods, digital resources, and flexible instructional design. The key components of professor’s competence are analyzed, along with their role in creating an engaging and sustainable learning environment. In conclusion, the article highlights the professor’s responsibility as an inspirer who cultivates critical thinking, values, and social engagement among students.
Keywords: generation Z; university professor; teaching role; teaching competence; professor’s responsibility